Some State Financial Segments of the Childbirth and Family Support System in Slovakia - Lentner, Csaba; Horbulák, Zsolt (Public Finance Quarterly, 2021)
Many countries around the world are struggling with the problem of declining fertility. In this study, we analyse the historical demographic context of Slovakia and present the tax and support instruments that the Slovak government uses to promote childbearing and parenting. The choice of the topic of this paper is in fact an indirect attempt to justify the Hungarian demographic and population policy measures. In our previous research, supported by empirical evidence, we found that Hungary, as a country with a similar level of development and in many respects similar to Slovakia, has been providing extensive tax and housing subsidies since the early 2010s, and we analysed how women of childbearing age and families relate to these subsidies. Do they have an impact on the propensity to have children? We have shown that the Hungarian government’s CSOK scheme and tax incentives are well received by young people, but that the promotion of childbearing depends on a number of factors beyond the financial incentives and subsidies. By analysing the situation in Slovakia, we also want to draw attention to the possible further development of the Hungarian system and other aspects of family formation.